The Relationship Between Maternal Characteristics and Compliance with Iron Tablet Consumption and the Incidence of Anemia in Third-Trimester Pregnant Women at Puskesmas Purwojati in 2023 - Priyantini; Citra Hadi Kurniati (UM Purwokerto Press, 2026)
Pregnancy-related anemia is a common condition that can lead to increased morbidity and mortality for both mothers and their infants. Anemia in pregnancy is often influenced by non-compliance with iron supplementation. The prevalence of anemia in pregnant women in Banyumas Regency was 17.09% in 2022, with Puskesmas Purwojati showing a higher prevalence of 25.34%. This study used a cross-sectional design with a quantitative approach. A total of 61 third-trimester pregnant women attending antenatal care at Puskesmas Purwojati were selected through purposive sampling. Data were collected using medical records and Maternal and Child Health (MCH) books. The incidence of anemia was defined as hemoglobin levels below 11 g/dl. Descriptive and inferential statistics, including Chi-square tests, were used for data analysis. The majority of participants were in the reproductive age group (91.8%) and employed (50.8%). A significant portion (55.7%) did not comply with the iron tablet regimen. The incidence of anemia was 28.6%. Significant relationships were found between maternal characteristics (age, parity, occupation) and anemia (p<0.05). Non-compliance with iron tablet consumption was strongly associated with anemia (p=0.000). Maternal characteristics such as age, parity, and occupation, along with non-compliance with iron supplementation, significantly contribute to the incidence of anemia in third-trimester pregnant women. Interventions aimed at improving compliance with iron supplementation, especially among high-risk groups, are essential to reducing anemia prevalence.